PREVALENCE OF INTESTINAL PARASITES IN FIGHTING COCKS OF CORO CITY, FALCON STATE, VENEZUELA - Cazorla P., Dalmiro (2013)
Cockfighting is an important and popular pastime that generates employment opportunities in Venezuela; however, fighting performance can be affected by gastrointestinal parasites. An epidemiological study was carried out during the last trimester of 2012 and first trimester of 2013 to determine the prevalence of gastrointestinal parasites in fighting cocks (Gallus gallus domesticus) (n=102) in the city of Coro, Falcon State, Venezuela. Faecal samples were analysed by direct test, Willis-Molloy (NaCl) and Faust (zinc sulphate) flotation methods and spontaneous sedimentation in tube technique. One or more intestinal protozoa or helminths were observed in 38 roosters (37.3%). Monoparasitism was observed in 8.8% cases and multiparasitism, including up to six parasite species occurred in some individuals. Strongyloides spp (20.6%), Capillaria spp (16.7%), Choanotaenia spp (12.8%), and Heterakis spp (6.9%) were the most prevalent enteric parasites. The cage cleaning frequency (p=0.009), type of feeder and drinker (p=0.01), disinfectant used (p=0.03), geophagy (p=0.007), frequency of treatment (p=0.009) and who prescribe it (veterinarian or bird owner) (p=0.0000) were potential risk factors related to the transmission and endemic maintenance of intestinal parasitism in fighting cocks.